Microbial Community of Healthy Thai Vegetarians and Non-Vegetarians, Their Core Gut Microbiota, and Pathogen Risk - Ruengsomwong, Supatjaree; La-ongkham, Orawan; Jiang, Jiahui; Wannissorn, Bhusita; Nakayama, Jiro; Nitisinprasert, Sunee (Journal of microbiology and biotechnology, 2016)
Pyrosequencing analysis of intestinal microflora from healthy Thai vegetarians and non-vegetarians exhibited 893 OTUs covering 189 species. The strong species indicators of vegetarians and non-vegetarians were and as well as bacteria close to with % relative abundance of 16.9 and 4.5-4.7, respectively. Core gut microbiota of the vegetarian and non-vegetarian groups consisted of 11 and 20 different bacterial species, respectively, belonging to Actinobacteria, Firmicutes, and Proteobacteria commonly found in both groups. Two species, and , had a prevalence of 100% in both groups. Three species, , , and , showed up in most vegetarians, whereas more diversity of , , various species of , , , and different species of and were found in most non-vegetarians. Considering the correlation of personal characters, consumption behavior, and microbial groups, the age of non-vegetarians showed a strong positive correlation coefficient of 0.54 ( = 0.001) to but exhibited a moderate one to and . Only a positive moderate correlation of body mass index and appeared. Based on the significant abundance of potential pathogens, the microbiota of the non-vegetarian group showed an abundance of potential pathogen varieties of , , and , whereas that of the vegetarian group served for only . These results implied that the microbiota of vegetarians with high abundance of and low potential pathogen variety would be a way to maintain good health in Thais.